Two Case Reports of Intravenous Leiomyomatosis with Hyaluronan Expression - Haruhisa Konishi; Iemasa Koh; Noriyuki Shiroma; Yukie Kidani; Satoshi Urabe; Norifumi Tanaka; Eiji Hirata; Koji Arihiro; Yoshiki Kudo (Case Reports in Obstetrics and Gynecology)
Intravenous leiomyomatosis (IVL) is a rare benign neoplasm. Herein, we describe two cases of IVL at different levels of progression. The tumor in Case 1 was extensive, invading the right atrium after a hysterectomy for a uterine myoma. The tumor temporarily responded to hormonal treatment; however, tumor regrowth occurred. In contrast, the tumor in Case 2 extended only to the pelvic veins and was revealed preoperatively. Hysterectomy and bilateral salpingo-oophorectomy were performed, resulting in the complete surgical resection of the tumor. In Case 2, no recurrence has been observed. Tumor samples were evaluated for hyaluronan expression using Alcian blue staining (with and without hyaluronidase digestion). The tumor in Case 1 stained strongly positive for hyaluronan while the tumor in Case 2 stained weakly positive for hyaluronan. In contrast, a large non-IVL uterine leiomyoma (control) stained negative for hyaluronan. These results suggest a relationship between tumor hyaluronan expression and IVL progression, similar to that in other cancers.